Adventure at Arms : On the Narrative Formation of Violence - Koppenfels, Martin von,; Mühlbacher, Manuel, (Philologie des Abenteuers ;, 2025)
Adventure fiction suggests that social conflicts can be displaced from the centre to the periphery of culture in order to be settled there by violent means. Its protagonists are endowed with extraordinary physical agency and a strange resilience to bodily and psychic wounds. This volume proposes a critical analysis of adventurous violence that foregrounds narratological issues as well as their socio-historical, political, and anthropological implications. Predicated on a broad diachronic perspective that challenges simple generalizations, the articles presented here cover a wide array of genres from ancient romance to the swashbuckling novel and a variety of contexts ranging from early modern state-building to colonialism, imperialism, and modern warfare.